Professionalizing public health education in the Eastern Mediterranean Region - Badr, Elsheikh; Ali, Sara; Assaf, Zainah; Belalia, Abdelmounim; Nuwayhid, Iman; Middleton, John; Czabanowska, Katarzyna; Squires, Neil; Al-Raddadi, Rajaa; Khader, Yousef (Frontiers in Public Health, 2025)
During the eighth EMPHNET Regional Conference, a roundtable session gathered eight public health leaders and academics from the Eastern Mediterranean Region (EMR) and Europe to discuss the professionalization of public health education with a focus on the EMR. The discussion reviewed the achievements, challenges, and prospects of public health education in the EMR and identified the tenets and strategies for professionalizing public health education and the public health workforce to better address health systems challenges. It also introduced the best practices and innovative approaches of public health professional education, and proposed strategies and interventions to strengthen public health education in the EMR toward professional and competency-based approaches. The findings highlighted that public health is not seen as an attractive career in the EMR due to the lack of clear career pathways and limited recognition. This has significant implications for education in the region, emphasizing the need to professionalize the public health workforce by leveraging international and regional experiences to address local challenges. The findings also underscored the importance of adopting competency-based approaches and pursuing professional recognition, credentialing, and regulation. In response, panelists recommended mapping and reviewing existing educational programs to develop competency-based frameworks and curricula tailored to the region’s context. They also stressed the importance of fostering partnerships between academia and public health organizations to provide experiential training and education in public health.